Ex vivo study of use of physiotherapy ultrasound in polymethylmethacrylate beads doped with methylene blue as an antibiotic carrier in small animals orthopedic surgery - Luigi Milanez Ávila Dias Maciel; Sheila Canevese Rahal; Alessandra Melchert; Tulio Genari Filho; Carlos Dias Maciel; Ivan Felismino Charas dos Santos (Ciência Animal Brasileira, 2021)
Polymethylmethacrylate bone cement is a standard material used as antibiotic carrier in the orthopedic surgery. The ultrasonic energy method is capable of triggering biological effects based on both thermal and non-thermal mechanisms. The aim of the current study is to analyze methylene blue dispersion in polymethylmethacrylate beads, in association with the acoustic field generated by non-thermal ultrasound. Forty-nine specimens were used, and each specimen comprised one polymethylmethacrylate bead (0.6-mm diameter) doped with methylene blue and deposited in gelatin sample. Forty test specimens were divided into four groups comprising 10 samples, each, based on different ultrasound intensities (Group 1: 1.0 W/cm²; Group 2: 1.5 W/cm²) and polymethylmethacrylate bead depths (A - 2 cm; B - 3 cm) in gelatin sample. The control group comprised other nine specimens and statistically differed from the other groups. All groups irradiated with ultrasound have shown statistically significant differences in methylene blue dispersion, except for Groups 2A and 2B. Methylene blue dispersion in gelatin among groups was 1A> 1B; 2A> 1A; 2B> 1A; 2A> 1B; and 2B> 1B. Low-intensity ultrasound enabled the highest methylene blue dispersion when polymethylmethacrylate bead was positioned superficial; bead depth associated with high-intensity ultrasound did not influence methylene blue dispersion. Keywords: phonophoresis; non-thermal ultrasound; osteomyelitis; treatment.